On The Emergence of Uzbek Hemeronymy and First Examples (Texas Journal of Philology, Culture and History, 2022)
The article describes the first examples of hemeronymy of the Uzbek language – the linguistic analysis of the names of newspapers published by the representatives of the Jadid movement, the views of the Jadids regarding the newspaper